Reversibility of symptomatic peripheral neuropathy with bortezomib in the phase III APEX trial in relapsed multiple myeloma: impact of a dose-modification guideline - Richardson, Paul G.; Sonneveld, Pieter; Schuster, Michael W.; Stadtmauer, Edward A.; Facon, Thierry; Harousseau, Jean-Luc; Ben-Yehuda, Dina; Lonial, Sagar; Goldschmidt, Hartmut; Reece, Donna; Bladé, Joan; Boccadoro, Mario; et al. (British journal of haematology, 2009)
The frequency, characteristics and reversibility of bortezomib-associated peripheral neuropathy were evaluated in the phase III APEX (Assessment of Proteasome Inhibition for Extending Remissions) trial in patients with relapsed myeloma, and the impact of a dose-modification guideline on peripheral neuropathy severity and reversibility was assessed. Patients received bortezomib 1.3 mg/m(2) (days 1, 4, 8, 11, eight 21-d cycles, then days 1, 8, 15, 22, three 35-d cycles); bortezomib was held, dose-reduced or discontinued depending on peripheral neuropathy severity, according to a protocol-specified dose-modification guideline. Overall, 124/331 patients (37%) had treatment-emergent peripheral neuropathy, including 30 (9%) with grade >or=3; incidence and severity were not affected by age, number/type of prior therapies, baseline glycosylated haemoglobin level, or diabetes history. Grade >or=3 incidence appeared lower versus phase II trials (13%) that did not specifically provide dose-modification guidelines. Of patients with grade >or=2 peripheral neuropathy, 58/91 (64%) experienced improvement or resolution to baseline at a median of 110 d, including 49/72 (68%) who had dose modification versus 9/19 (47%) who did not. Efficacy did not appear adversely affected by dose modification for grade >or=2 peripheral neuropathy. Bortezomib-associated peripheral neuropathy is manageable and reversible in most patients with relapsed myeloma. Dose modification using a specific guideline improves peripheral neuropathy management without adversely affecting outcome.
Gesehen am 14.01.2022